Undergraduate Researchers' Attainment of Graduate Degrees - (:unkn) unknown (My University, 2017)
The existing literature suggests that faculty-student interactions have a positive effect on students’ pursuits to attain undergraduate and graduate degrees. However, some scholars argue that the type of interactions and the extent to which students benefit vary between student sub-populations. Understanding who engages in undergraduate research at urban research universities and who goes on to attain graduate degrees are essential to expanding the knowledgebase and policy-making at the institutional level. Investigating the efficacy of undergraduate research programs at urban institutions that have access to diverse populations will allow for analyses with different samples. The goal of this research was to create a dataset that allowed for the documentation of the demographic and academic makeup of a population of students that engaged in a university wide centralized undergraduate research intervention at an urban research university. The descriptive analysis included demographic and academic performance information, as well as timing and duration of engagement in undergraduate research. This study included a logistic regression analysis to examine differences in likelihood of graduate degree attainment, in relationship to race/ethnicity, financial need, timing, duration, and academic performance.